Pusat Informasi Pariwisata Terpadu di Surakara - Setiawan, Kurnia; , Dr. Ir Arya Ronald; , Suryaning Setyowati, ST., MT (2016)
Surakarta is a city full of history and cultural nuances, proud Javanese tradition. A place that will make you amazed by the diverse attractions of ancient Javanese cultural heritage. The cultural heritage of this from time to time developed into a tourist attraction to meet the diverse human desires. Interest and motivation high rating, must be balanced by an information and promotion activities attractions are planned, directed, integrated and effective. Tourism Information Center as a building that serves accommodate activities related to tourism information and culture in the city of Surakarta, Integrated Tourism Information Center has a major role for tourism and culture in the city of Surakarta as to introduce an integrated tourism to tourists , both domestic and foreign.